PROTOTIPE SISTEM INFORMASI SUMBER DAYA INVESTASI : STUDI KASUS BALAI SUMBER DAYA INVESTASI PUSAT PEMBINAAN SUMBER DAYA INVESTASI BADAN PEMBINAAN KONSTRUKSI KEMENTERIAN PEKERJAAN UMUM - Hepi Nuryadi; Moedjiono Moedjiono; Samidi Samidi (Fakultas Ilmu Komputer dan Desain - Unsurya, 2017)
Development investment resources information systems can mean developing a new system to replace the old system or improve the existing system in a company, institutions or government agencies, including Balai Sumber Daya Investasi (Balai SDI) is supervised by Pusat Pembinaan Sumber Daya Investasi, which is one Eselon II in Badan Pembinaan Konstruksi Ministry of Public Works which has the duty to formulate policies based resource infrastructure investment policies that have been established. ). Since its establishment until now Balai SDI hasn’t had a system of integrated applications that manage the construction market data, materials and construction equipment throughout Indonesia. The scope of the Investment Resource Information System developed include: construction market data, market potential data construction, material data, the data of AMP (Asphalt Mixing Plant), Quarry data, cement Statistics data, the data of Pt Pertamina petroleum asphalt, and construction equipment. This research is type of Applied Research (Applied Research). Information systems development method using Prototype model. Methods of data collection by observation, sampling data, literature, and interviews with a selected sample using purposive sampling method. The method used in analyzing and designing a system is a method of Object Oriented Analysis and Design (Object Oriented Analysis and Design) using Unified Modeling Language (UML). System testing techniques with black-box testing approach. Validation testing using the Focus Group Discussion. The quality of the resulting software was tested by four models of software quality characteristics of ISO 9126, namely: functionality, reliability, usability, and efficiency using the questionnaire method. The results are in the form of websites Sistem Informasi Sumber daya Investasi that have a very good level of quality and function can provide construction market information in order to increase competitiveness and investment in the construction sector in Indonesia